1919: The Canadian Labour Revolt - Kealey, Gregory S. (Labour / Le Travail, 1984)
This essay attempts to place Canadian workers' 1919 militancy in a national and international context. Utilizing freshly compiled strike data and focusing on events outside of Winnipeg, the paper argues that the 1919 revolt was nation-wide and part of the international post-war revolutionary upsurge. The new prominence of women and immigrant workers, reflecting the drive for industrial unionism, is emphasized.